2007
DOI: 10.3748/wjg.v13.i27.3767
|View full text |Cite
|
Sign up to set email alerts
|

Combination of thrombolytic therapy and angioplastic stent insertion in a patient with Budd-Chiari syndrome

Abstract: A 31-year-old female who had well-established polycythemia vera one year before, presented with the sudden onset. She had severe ascites and hepatic encephalopathy 12 d prior to admission. Real-time ultrasonography revealed a supra hepatic thrombosis extending toward the inferior vena cava (lVC). Thrombolytic therapy with systemic streptokinase (250000 IU loading + 100000 IU/h infusion) was started. At the end of 72 h infusion, the patient's general condition improved. A color Doppler ultrasonography then show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…El tratamiento médico con anticoagulación no es el adecuado y se debe complementar siempre con un procedimiento de nueva perfusión de los vasos ocluidos, ya sea quirúrgica o endovascular; la anticoagulación sola tiene una mortalidad del 80 % en un periodo de dos años. Los objetivos del tratamiento en el síndrome de Budd-Chiari son disminuir la congestión hepática y la ascitis, y evitar el deterioro hepático [23][24][25] .…”
Section: Discussionunclassified
“…El tratamiento médico con anticoagulación no es el adecuado y se debe complementar siempre con un procedimiento de nueva perfusión de los vasos ocluidos, ya sea quirúrgica o endovascular; la anticoagulación sola tiene una mortalidad del 80 % en un periodo de dos años. Los objetivos del tratamiento en el síndrome de Budd-Chiari son disminuir la congestión hepática y la ascitis, y evitar el deterioro hepático [23][24][25] .…”
Section: Discussionunclassified
“…Numerous factors, including malignancy, myeloproliferative disease, rheumatological disorders, hypercoagulability, infection and ulcerative colitis are potential etiological factors of thrombosis. However, the causes remain unidentified in 16–35% cases (13,16). Kuo et al (17) studied three cases of BCS complicated by hepatic vein thrombosis, in which the hepatic veins were recanalized without stenosis or occlusion following the removal of the thrombus by thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In western countries, BCS usually results from hypercoagulability (including myeloproliferative disorders, oral contraceptives and pregnancy)-induced thrombosis in one to three hepatic veins, or even in the IVC, which is characterized by an acute onset (1). It has been demonstrated that these patients may be treated with anticoagulation and thrombolytic (streptokinase) therapies to dissolve the thrombi in the hepatic veins (2,3). However, in eastern countries, membranous obstruction of the IVC and/or the hepatic veins is the most frequently occurring underlying cause of BCS (4), and this is most likely induced by organized thrombi or congenital factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation